Effect of hyperoxic gas mixture on functional status and performance of skiers and biathletes - Koriagina, J.; Reutskya, E.; Simonova, K. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Some authors point out the oxygen mixtures most efficient use during the maximum and submaximal loads. However, among the researches there is no consensus about the oxygen support effectiveness before exercises (Sperlich B.,et al, 2011). The purpose of this study was to determine the effect of hyperoxic gas mixture with an oxygen content of 93% on the organism functional state and the athletes' performance during the maximum test.